Genomic Confirmation of Borrelia garinii , United States - Rudenko, Natalie; Golovchenko, Maryna; Horak, Ales; Grubhoffer, Libor; Mongodin, Emmanuel F.; Fraser, Claire M.; Qiu, Weigang; Luft, Benjamin J.; Morgan, Richard G.; Casjens, Sherwood R.; Schutzer, Steven E. (Emerging infectious diseases, 2023)
Lyme disease is a multisystem disorder primarily caused by Borrelia burgdorferi sensu lato. However, B. garinii, which has been identified on islands off the coast of Newfoundland and Labrador, Canada, is a cause of Lyme disease in Eurasia. We report isolation and whole-genome nucleotide sequencing of a B. garinii isolate from a cotton mouse (Peromyscus gossypinus) in South Carolina, USA. We identified a second B. garinii isolate from the same repository. Phylogenetic analysis does not associate these isolates with the previously described isolates of B. garinii from Canada.